Alteration of Loperamide-Induced Prostate Relaxation in High-Fat Diet-Fed Rats - Sheng-Lung Hsu; Hsien-Hui Chung; I-Hung Chen; Yat-Ching Tong (The Scientific World Journal)
Objective. To investigate the change of loperamide-induced prostate relaxation in rats fed with high-fat diet (HFD). Materials and Methods. Adult male Wistar rats were divided into 2 groups: (1) control rats fed with normal chow and (2) rats fed with HFD for 6 months. The prostate was removed for histology study. Isolated prostate strips were hung in organ bath and precontracted with 1 μmol/L phenylephrine or 50 mmol/L KCl. The relaxation responses to loperamide 0.1 to 10 μmol/L were recorded. Western blotting analyses were performed for prostate μ-opioid receptors (MOR) and ATP-sensitive potassium (KATP) channel proteins: sulfonylurea receptor (SUR) and inwardly rectifying potassium channel (Kir) 6.2 subunits. Results. Body weight, prostate weight, plasma levels of glucose, insulin, triglyceride, and cholesterol, as well as systolic blood pressure, were significantly increased in the HFD rats. Histology showed prostatic hyperplasia in the HFD rat prostate. Prostatic relaxation induced by loperamide was markedly reduced in HFD when compared to the control. Protein expressions of MOR, SUR, and Kir 6.2 were decreased in HFD-fed rats. Conclusion. Loperamide-induced prostate relaxation is decreased in HFD rats due to reduced MOR and KATP channel expressions.